2014
DOI: 10.5755/j01.erem.67.1.6240
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Water Management in Small Scale Irrigation Schemes: the Case of the Ethiopian Rift Valley Lake Basin

Abstract: Appraisals of irrigation water management scenarios are crucial in project performance monitoring. A comprehensive irrigation water management study has been conducted on four small scale irrigation schemes in the Ethiopian rift valley lake basin. It is observed that from 147 irrigators 68% faced irrigation water supply unreliability, 79.1% encountered unfair distribution of water and 66 % underwent through timeliness problem in water distribution occasionally. All the investigated schemes witnessed a weak (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…This study noted that limited abilities, skills and knowledge of farmers in operation and maintenance of the scheme affected the efficiencies at the scheme. These results concur with the findings of Dejen et al [19] and Ulsido [20] who found out that limited trainings on irrigation water management leads to low performance of an irrigation scheme. Yami and Snyder [21] extended that farmers' trainings in irrigation water management are crucial in ensuring sustainable irrigation development.…”
Section: Water Delivery Performance Indicatorssupporting
confidence: 92%
“…This study noted that limited abilities, skills and knowledge of farmers in operation and maintenance of the scheme affected the efficiencies at the scheme. These results concur with the findings of Dejen et al [19] and Ulsido [20] who found out that limited trainings on irrigation water management leads to low performance of an irrigation scheme. Yami and Snyder [21] extended that farmers' trainings in irrigation water management are crucial in ensuring sustainable irrigation development.…”
Section: Water Delivery Performance Indicatorssupporting
confidence: 92%
“…Irrigation practices in the nation are mainly traditional [20] and range from medium to large-scale. Small-scale irrigation is not well practiced in the nation [21]. However, small-scale irrigation plays an important role in maximizing food production and contributing towards food security in Ethiopia and other Sub-Saharan countries [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the Rift Valley Lake Basin of Ethiopia showed that soil salinity/acidity, waterlogging, and communicable and noncommunicable diseases were the main limitations as well as depletion of water, and continuous maintenance needs and inefficient water management were the challenges of small scale-irrigation. Such factors meant the production gain from irrigated agriculture was below the expected value (Ulsido et al, 2013;Ulsido and Alemu, 2014). Consistent problems were also observed in Namibia (Fiebiger et al, 2010).…”
Section: Livelihood Status Of Respondentsmentioning
confidence: 56%